O processo de produção escrita em livros didáticos de língua portuguesa: do planejamento à revisão - Eloisa Helena Rodrigues Guimaraes (2009)
This thesis presents a set of analyses of text production activities that integrates five didactic collections from 5th to 8th grades of Ensino Fundamental evaluated and approved by the Programa Nacional do Livro Didático (National Program of Didactic Book) PNLD 2008. The corpus was defined based on researches that indicated the most adopted collections sent by the organs responsible for the public politics of distribution of didactic books to the state schools in Belo Horizonte. The focus on these analyses concentrates on verifying the efficiency of thepotential of those collections in the subject of development in the ability of writing. The research aimed at verifying if the activities of self-evaluation and text revisions proposed on those collections offer the students subsidies to develop the ability of reflection on their own writingproduction. This interest is motivated by the understanding that taking these procedures into consideration can favor the acquisition of abilities that lead students to become efficient text producers, capable of evaluating critically their own productions, promoting alterations wherethey judge necessary in accordance with the principles that rule textuality. The theoretical support of this research concentrates on the current discussions on conceptions of language, text, subject and textual genres that have influenced the production of didactic books on Portuguese in Brazil since the last decade of the 20th century, and on the reflections about the sociointeractionist character of writing. The analyses point out that the perception that what must be considered in text evaluation is not a task that can easily be internalized by the students, especially when thisprocedure is not systematically proposed as a part of the production process. For this reason, to get the students to evaluate their own production efficiently it is necessary that the didactic books, besides establishing clearly the criteria to be observed in the final version of the text, transform this task into an integrate part of the production process.Key words: didactic book, PNLD, text production, writing, textual gender